Curcumin–Triterpene Type Hybrid as Effective Sonosensitizers for Sonodynamic Therapy in Oral Squamous Cell Carcinoma - Katarzyna Sowa-Kasprzak; Małgorzata Józkowiak; Dorota Olender; Anna Pawełczyk; Hanna Piotrowska-Kempisty; Lucjusz Zaprutko (Pharmaceutics, 2023)
Sonodynamic therapy (SDT) is a non-invasive therapeutic modality in cancer treatment that combines low-intensity ultrasound (US) and sonosensitizers. Tumor cells are destroyed through the synergistic effects of ultrasound and a chemical sonosensitizer. This study focused on the synthesis and in vitro evaluation of the sonodynamic effect of natural curcumin, triterpene oleanolic acid, and their semi-synthetic derivatives on tongue cancer SCC-25 and hypopharyngeal FaDu cell lines. The combination of the tested compounds with sonication showed a synergistic increase in cytotoxicity. In the group of oleanolic acid derivatives, oleanoyl hydrogen succinate (6) showed the strongest cytotoxic effect both in the SCC-25 and FaDu cell lines. Comparing curcumin (4) and its pyrazole derivative (5), curcumin showed a better cytotoxic effect on SCC-25 cells, while curcumin pyrazole was more potent on FaDu cells. The highest sonotherapeutic activity, compared to its individual components, was demonstrated by a structural linker mode hybrid containing both curcumin pyrazole-oleanoyl hydrogen succinate units within one complex molecule (7). This study can be beneficial in the context of new perspectives in the search for effective sonosensitizers among derivatives of natural organic compounds.